IZI To Success: The Impact Of The Productive Zakat Empowerment Program On The Welfare Of Beneficiaries By The Indonesian Zakat Initiative (IZI) In North Sumatra - Nurul Husna; Muhammad Habibi Siregar (Universitas Trunodjoyo Madura, 2023)
The objective of this research is to understand the mechanism and assess the impact of the IZI To Success program implemented by the Indonesian Zakat Initiative (IZI) in North Sumatra on the welfare of beneficiaries. The approach used is a descriptive qualitative approach with a case study strategy. Data collection techniques for this research include observation, interviews, and literature review. The data analysis technique in this study consists of three stages: 1) Data reduction (simplification and abstraction of data), 2) Data presentation (organizing information in the form of narrative texts), and 3) Concluding. This study involved six informants from the IZI To Success program, divided into the